2020
DOI: 10.1002/hrm.22013
|View full text |Cite
|
Sign up to set email alerts
|

Crafting job demands and employee creativity: A diary study

Abstract: People are more creative on some days than others. Studying how individuals generate creative ideas from day to day could contribute to knowledge regarding the causes of such within-person variations and have practical implications for improving employee creativity across time. By adopting a dynamic resource allocation perspective and a repeated-measure diary design, we developed and examined a theoretical model focusing on the within-person processes of employee creativity. Specifically, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 116 publications
2
16
0
Order By: Relevance
“…First, this study confirms that strengths-based job crafting is an important antecedent variable of employee creativity. The job crafting literature has provided several theoretical perspectives to explain how job crafting influences individual creativity, such as job demands and resource allocation ( Beck and Schmidt, 2018 ; Sun et al, 2020 ). However, these studies have mainly focused on the “job” part, and the “person” part have been largely overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, this study confirms that strengths-based job crafting is an important antecedent variable of employee creativity. The job crafting literature has provided several theoretical perspectives to explain how job crafting influences individual creativity, such as job demands and resource allocation ( Beck and Schmidt, 2018 ; Sun et al, 2020 ). However, these studies have mainly focused on the “job” part, and the “person” part have been largely overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…How to enhance employee creativity is a focal concern for academics and practitioners ( Amabile et al, 2005 ; Rietzschel et al, 2016 ; Wu et al, 2020 ). The self-management practice of job crafting, or the changes that employees make to their jobs, has been proved to be an important antecedent of employee creativity ( Bruning and Campion, 2018 ; Sun et al, 2020 ; Wang and Lau, 2021 ). However, most existing studies focused on the top-down job design interventions, which are generally found to be less effective than researchers and practitioners hope ( Nielsen et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown that employees with a high sense of self-worth will engage in more proactive behavior. 31 On the contrary, when employees perceive a higher sense of role overload, their available time and resources will decrease, which will reduce employees’ ability to control their work and lead to their reduced proactive behavior. 32 …”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have also shown that employees with a high sense of selfworth will engage in more proactive behavior. 31 On the contrary, when employees perceive a higher sense of role overload, their available time and resources will decrease, which will reduce employees' ability to control their work and lead to their reduced proactive behavior. 32 Accordingly, this paper has put forward the moderating effect of reciprocation wariness on perceived leader trust and the sense of self-worth (Hypothesis 1), the moderating effect of reciprocation wariness on perceived leader trust and the sense of role overload (Hypothesis 2), and the influence of…”
Section: A Moderated-mediated Modelmentioning
confidence: 99%